Performance-Based Placement of Manufactured Viscoelastic Dampers for Design Response Spectrum - Nakamura, Yutaka; Hanzawa, Tetsuya; Nomura, Takeshi; Takada, Tomokazu (Frontiers in Built Environment, 2016)
In this study, a viscoelastic damper (VED) is developed by using a VE material with low temperature dependence, and a performance-based placement-design procedure of VEDs is developed for finding the storywise distribution of VEDs in a building such that each peak interstory drift coincides with the prescribed value. The mechanical properties of the employed VED’s dependence on amplitude and frequency of the excitation as well as material temperature are taken into account and a mechanical nonlinear four-element model that comprises two dashpot elements and two spring elements is proposed for the VED. The developed performance-based design procedure utilizes equivalent linearization of the VED and the expanded complete quadratic combination (CQC) method, which involves modal analysis with complex eigenvalue analysis. An equivalent linear Voigt model of the VED is determined by the prescribed peak interstory drift and the fundamental natural period of the structure for which the VEDs are installed. Seismic response analyses are carried out for high-rise building models installed with the necessary number of wall-type VEDs, with the results demonstrating the effectiveness and validity of the proposed performance-based placement-design procedure.